Halal Barcode Scanner Prototype in Android using Client Side Processing with Json Technology - Noor Munirah, Marzuki; Tuty Asmawaty, Abdul Kadir; A. S., Shibghatullah (2014)
Halal industry has becoming a steady growth industry in Malaysia since people including Muslim and non-Muslim are already alert about this issue due to its hygienic production. However, consumers nowadays are facing few difficulties regarding Halal recognition status as the logo has been duplicated and contacting JAKIM directly via telephone call or browsing web portal is slow and tiring. In certain circumstances, the use of existing technology like Radio-frequency Identification (RFID) is expensive and unaffordable to local communities. Besides, reading the barcode itself will burden consumer as they need to remember all sorts of codes available in stores. Therefore, the usage of Smartphone, barcode,scanner and camera will be tested to recognize and split information from a barcode. The results will be analysed by developing Halal Barcode Recognition Status using Android Smartphone by matching the scan barcode to the database. Client server architecture is used to migrate data stored in server database and save to local database. The information will be extracted to recognize its halal status. Based on the testing, the system is capable to recognize the Halal status; however it needs further research for commercial use.